A study of PTEN expression in endometrial hyperplasia and endometrioid type of endometrial carcinoma - Dr. M. Shanmugapriya; Dr. M. Sudha; Dr. Geetha Prakash (Tropical Journal of Pathology and Microbiology, 2017)
Background: To analyze the role of PTEN expression in hyperplastic and neoplastic endometrium by immunohistochemistry and to find the grades of PTEN expression in neoplastic, hyperplasic and normal endometrium.Methods: 100 numbers of endometrial samples were studied retrospectively. The tissue were fixed in formalin and taken up for routine histopathological and immunohistochemistry studies.Results: In our study PTEN is well expressed in a score of 2+ and 1+ in cyclical endometrium and hyperplasia without atypia whereas altered PTEN expression was noted in atypical hyperplasias and endometroid type of endometrial carcinoma in a score of 0and 1+.Conclusion: The current study proved that PTEN expression is down regulated in endometrial pathological condition. Immunohistochemical evaluation of PTEN expression was useful in screening precancerous hyperplasia lesions and detecting earliest stage of endometrial carcinogenesis.